Exploring the determinants of chloride homeostasis in neurons using biophysical models - Düsterwald, Kira M (Department of Human Biology, 2019)
Fast synaptic inhibition in the nervous system depends on the transmembrane flux of Cl ions via activated GABAA and glycine receptors. As a result, changes to the neuronal driving force for Cl- are thought to play pivotal roles in many physiological and pathological brain processes. Established theories regarding the determinants of Cl- driving force have recently been questioned based on new experimental data. However, it is experimentally difficult to distinguish the respective contributions of the multiple, dynamically interacting mechanisms which may be important in Cl- homeostasis. Here I present biophysical models of Cl- homeostasis using the pump-leak formulation. By means of numerical and novel analytic solutions, I demonstrate that the Na+/K+-ATPase, ion conductances, impermeant anions, electrodiffusion, water fluxes and cation-chloride cotransporters (CCCs) play roles in setting the Cl- driving force. Importantly, I show that while impermeant anions can contribute to setting [Cl- ]i in neurons, they have a negligible effect on the driving force for Cl locally and cell-wide. In contrast, I demonstrate that CCCs are well-suited for modulating Cl- driving force and hence inhibitory signalling in neurons. This prediction is supported by a meta-analysis of multiple experimental studies, which demonstrates a strong correlation between the expression of the cationchloride cotransporter KCC2 and intracellular Cl concentration. My findings reconcile recent experimental findings and provide a framework for understanding the interplay of different chloride regulatory processes in neurons.